2019
DOI: 10.1101/674846
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physical activity, aerobic fitness and brain white matter: their role for executive functions in adolescence

Abstract: Highlights:· Aerobic fitness level, but not physical activity, is associated with white matter properties in several white matter tracts in the brain.· The relationship between aerobic fitness and working memory was moderated by fractional anisotropy of the body of corpus callosum and in the right superior corona radiata.· The relationship between physical activity and working memory was moderated by fractional anisotropy of the body and genu of corpus callosum. Declarations of interest: noneAbbreviations: CAN… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 61 publications
1
14
1
Order By: Relevance
“…Nevertheless, they showed different associations with executive control and its underlying brain processes. Although the aerobic fitness has been shown to be more strongly associated with brain structural measures than physical activity (Ruotsalainen et al, 2019;Ruotsalainen et al, 2020), we did not find any relationship between aerobic fitness and brain oscillatory dynamics underlying anticipatory attention allocation. However, in behavioral measures higher aerobic fitness was related to higher drift rate values in the selective attention/inhibition task.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Nevertheless, they showed different associations with executive control and its underlying brain processes. Although the aerobic fitness has been shown to be more strongly associated with brain structural measures than physical activity (Ruotsalainen et al, 2019;Ruotsalainen et al, 2020), we did not find any relationship between aerobic fitness and brain oscillatory dynamics underlying anticipatory attention allocation. However, in behavioral measures higher aerobic fitness was related to higher drift rate values in the selective attention/inhibition task.…”
Section: Discussioncontrasting
confidence: 89%
“…The dynamic interaction between hemispheres, modulating the processing capacity of the brain, is proposed to occur via the corpus callosum (Banich, 1998;Qin et al, 2016). A recent study by our group (Ruotsalainen et al, 2020) investigated the connection between both aerobic fitness and physical activity with the white matter in adolescents using MRI and fractional anisotropy (assessing microstructural changes in the brain's white matter). Although the main results in this study showed that only the level of aerobic fitness was related to white matter properties, it was also described that the level of fractional anisotropy in the body of the corpus callosum could moderate the relationship between physical activity and working memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we studied the association of both aerobic fitness (estimated using a 20‐m shuttle run test [SRT]) and moderate‐to‐vigorous physical activity (measured with accelerometers) with voxel‐wise homotopic connectivity. Based on our previous findings showing an association between aerobic fitness and corpus callosum microstructure (Ruotsalainen et al., 2020), we hypothesized that aerobic fitness, but not physical activity, would be associated with 13–16‐year‐old adolescents’ homotopic connectivity. Further, in contrast to longer range functional connections, we studied the associations of physical activity and aerobic fitness with the brain's local functional connectivity using ReHo.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of structural connectivity have shown that physical activity and aerobic fitness are related to the white matter structure connecting the brain's hemispheres, namely the corpus callosum, in children (Chaddock‐Heyman et al., 2014, 2018) and adolescents (Ruotsalainen et al., 2020). Although functional connectivity cannot be explained solely by considering the brain's structural connectivity, many studies have demonstrated that functional connectivity at least partly reflects underlying structural connections (Mollink et al., 2019; Shah et al., 2018; Van Den Heuvel et al., 2009).…”
Section: Introductionmentioning
confidence: 99%